New Magnetostratigraphic Insights From Iceberg Alley on the Rhythms of Antarctic Climate During the Plio‐Pleistocene. Issue 2 (9th February 2021) - Reilly, Brendan T.; Tauxe, Lisa; Brachfeld, Stefanie; Raymo, Maureen; Bailey, Ian; Hemming, Sidney; Weber, Michael E.; Williams, Trevor; Garcia, Marga; Guitard, Michelle; Martos, Yasmina M.; Pérez, Lara F.; et al.
Abstract: International Ocean Discovery Program (IODP) Expedition 382 in the Scotia Sea's Iceberg Alley recovered among the most continuous and highest resolution stratigraphic records in the Southern Ocean near Antarctica spanning the last 3.3 Myr. Sites drilled in Dove Basin (U1536/U1537) have well‐resolved magnetostratigraphy and a strong imprint of orbital forcing in their lithostratigraphy. All magnetic reversals of the last 3.3 Myr are identified, providing a robust age model independent of orbital tuning. During the Pleistocene, alternation of terrigenous versus diatomaceous facies shows power in the eccentricity and obliquity frequencies comparable to the amplitude modulation of benthic δ 18 O records. This suggests that variations in Dove Basin lithostratigraphy during the Pleistocene reflect a similar history as globally integrated ice volume at these frequencies. However, power in the precession frequencies over the entire ∼3.3 Myr record does not match the amplitude modulation of benthic δ 18 O records, suggesting Dove Basin contains a unique record at these frequencies. Comparing the position of magnetic reversals relative to local facies changes in Dove Basin and the same magnetic reversals relative to benthic δ 18 O at North Atlantic IODP Site U1308, we demonstrate Dove Basin facies change at different times than benthic δ 18 O during intervals between ∼3 and 1 Ma. These differences are consistent with precession phase shifts and suggest climate signals with a Southern Hemisphere summer insolation phase were recorded around Antarctica. If Dove Basin lithology reflects local Antarctic ice volume changes, these signals could represent ice sheet precession‐paced variations not captured in benthic δ 18 O during the 41‐kyr world. Key Points: Extended composite and correlated equivalent depth scales are presented for Antarctic proximal International Ocean Discovery Program Sites U1536 and U1537 U1536 and U1537 have excellent magnetostratigraphy and clear imprint of orbital variations in their lithology Changes in terrigenous versus diatomaceous Dove Basin facies are out of phase with benthic δ 18 O during intervals between 3.3 and 1 Ma